ICT and the demand for energy: Evidence from OECD countries - Sascha Rexhaeuser; Patrick Schulte; Heinz Welsch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper analyzes the relationship between information and communication technology (ICT) and energy demand. We construct a comprehensive cross-country cross-industry panel data set covering 13 years, 10 OECD countries, and 27 industries. Using up to 2889 country-industry observations, we find that: (1) ICT capital is associated with a significant reduction in energy demand. (2) This relationship differs with regard to different types of energy. ICT use is not significantly correlated with electricity demand, but is significantly related to a reduction in non-electric energy demand. That is, ICT use comes with a reduction in total energy demand and an increase in the relative demand for electric over non-electric energy.
urn:nbn:de:bsz:180-madoc-353900
Keywords: O33; O44; Q41; Q43; 330; technical change; ICT; energy demand; energy efficiency; energy mix; Green IT; cross-country cross-industry data; environmental policy